COACHING SEBAGAI STRATEGI MANAJERIAL DALAM PENGEMBANGAN KINERJA GURU PADA PERSPEKTIF MANAJEMEN SUMBER DAYA MANUSIA DI SDIT DARUT TAUHID GABUS - Ulfana Hidayati; Barokah Isdaryanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines coaching as a managerial strategy for improving teacher performance from a human resource management perspective at SDIT Darut Tauhid Gabus. The study is grounded in observed variations in teacher performance, particularly in discipline, lesson planning, classroom management, and assessment alignment, which indicate the need for a systematic and sustainable human resource development approach in schools. This research aims to analyze the implementation of coaching as a managerial strategy and its contribution to improving teacher performance and learning quality. A qualitative descriptive approach was employed using interviews, observations, and documentation as data collection techniques. The findings reveal that coaching implemented by the principal contributes to improvements in teacher professionalism, instructional quality, classroom management, and work discipline. Furthermore, coaching fosters reflective teaching practices and promotes the emergence of a continuous improvement culture within the school. The study concludes that coaching functions not only as a supervisory mechanism but also as a strategic human resource development approach that enhances teacher performance and improves the quality of learning at the school level.